Synthesis of Pro Drug Polyester and Control Release - Abd Alrazaak M, Abeer (Al-Nahrain Journal of Science, 2017)
Lactic acid was used as difunctional spacer could reacted with glycerol gave its corresponding ester derivative with remain the hydroxyl groups of lactate units which reacted with carboxyl group of Mefenamic acid forming ester attachment, the prepared pro drug have many development, it could enhanced the drug with easier hydrolysis through ester-ester groups with extended the arm pendant substituted drug. The action of polymeric drugs depends on hydrolytic and cleavage of the drug moiety from the polymer, this give advantages of late and sustained release of drug over long time with decrease of side effects, the modification percentage test was carried out, also it was characterized by FTIR and 1H-NMR spectroscopes. Controlled drug release was deliberate by using different pH values at 37℃. Thermal stability of the drug polymer was observed, indicated the protection of drug with longer expire date.